Robert Bellah - en stor sociolog - Kühle, Lene (Religionsvidenskabeligt Tidsskrift, 2013)
English abstract: Bellah, who died in 2013, was a grand sociologist. His name is often connected to the concept civil religion, a concept introduced by Bellah in a 1967-article. During the 1970’s Bellah revised his thinking on civil religion, but he was unsuccessful in finding resonance for it. The legacy of Bellah is therefore not so much to be found within the specific study of civil religion. His legacy lies in his engagement with connecting mainstream sociology with the Humanities. Dansk resumé: Robert N. Bellah, som døde i 2013, var en stor sociolog. Hans navn forbindes i høj grad med begrebet civilreligion, som Bellah introducerer i en artikel fra 1967. Bellah reviderede i løbet af 1970’erne sin tænkning om amerikansk civilreligion, men de nye forståelser vandt til Bellahs store frustration ingen genklang. Den arv, som Bellah efterlader sig, består derfor kun i mindre grad af forståelsen af civilreligion, men i højere grad af hans varige engagement i at forbinde mainstream-sociologi med kulturvidenskab.